Quorum Sensing Inhibition pada Pembetukan Biofilm Salmonella typhi dengan Ekstrak Daun Cincau Hijau (Cyclea barbata Miers) - Anjaini, Jefri; Simangunsong, Tohap; Irawan, Hery (Jurnal Biologi Tropis, 2024)
Salmonella is one example of bacteria that can contaminate fishery products. It is one of the bacteria that most commonly infects people through contaminated food and drink. One management to reduce Salmonella in fishery products is using Biofilm. The biofilm mechanism formed from Salmonella typhi type bacteria can be inhibited from several intervention strategies that are able to disrupt and prevent biofilm formation. Green grass jelly leaf extract has antibacterial activity against S. typhi which is indicated by the formation of an inhibition zone due to the activity of flavonoid compounds. denaturing proteins and damaging bacterial cell membranes, flavonoids can also function as antibacterials by forming complex compounds that attack extrinsic proteins and inhibit biofilm formation by inhibiting the expression of icaA and icaD genes. flavonoids form complex compounds against extracellular proteins, which disrupt the integrity of the bacterial cell membrane. It does so by denaturing bacterial cell proteins and damaging the cell membrane beyond repair.